Histogenesis of gut associated lymphoid tissues(GALT) in Catla catla (Hamilton) - Suresh, N; Ranganathan, L S (Indian Journal of Fisheries, 2014)
The present study focussed on the ontogeny of gut associated lymphoid tissues(GALT) in the Indian major carp, Catla catla at early developmental stages.Gut appeared as a small tube on third day of post hatch and there is no evidenceof lymphoid cells at this stage. Few leucocytes were detected on fifth day of posthatch and thereafter the leucocytes were increased in subsequent stages. Byfifteen days of post hatch C. catla attains the adult component gut and there isno accumulation or aggregation of lymphoid cells along the entire length of thegut. The presence of isolated leucocytes in the gut epithelium and lamina propriaindicates that GALT appeared to be of diffused nature.